Early-age Temperature Distribution in a Massive Concrete Foundation. (2016) - Kuriakose, Bennet; Rao, B. Nageswara; Dodagoudar, G.R.
Abstract: Early-age cracking appertains to massive concrete elements on the account of thermal gradients due to highly exothermic hydration reaction of cement. The cracking as a result of thermal strains can in turn lead to undesirable consequences on structural durability. In this paper, a degree of hydration-based finite element simulation procedure is developed and implemented in order to determine the temperature distribution of young concrete within a massive solid circular raft foundation. The developed finite element program is validated with experimental results available in the literature. The information regarding temperature development can effectively be used to compute thermal stresses while designing the massive foundation for structural as well as durability considerations. Appropriate measures can also be taken to bring down the temperature levels during the phased casting operations so as to avoid early-age cracking problems.